Use of the capital markets by exporting SMEs in Barranquilla - Lechuga Cardozo, Jorge Isaac; Muñoz Querales, Edgardo Enrique (Universidad Francisco de Paula Santander, 2015)
This article is the result of a research, whose objective was to analyze the capital market products most used by exporting SMEs in the city of Barranquilla, the descriptive method was applied, with the survey research technique, to a stratified sample of 45 companies. The type of research is quantitative and for the approach of the research, a documentary review of the situation of the small and medium exporting companies in the local environment was carried out, as well as a study to know the degree of use that these companies have of the products of the capital market, identifying the benefit that the SMEs have when using efficiently the securities offered by the financial sector. It was concluded that there is a low participation in the consumption of capital market products by exporting SMEs with a negative effect on the activities of the export sector, particularly in the city of Barranquilla, which impacts the economic results of the country and the region.